Study on Simulation and Design of Various PI Controller for a Non-Interacting Systems: An Approach to Conventional and Computational Algorithms - Rajaraman, Janani; Sarangan, Jayanth (Current Approaches in Science and Technology Research Vol. 1, 2021)
Various conventional and computational algorithms for developing a PI controller are investigated in this research. Many controllers used in the industries are conventional PID controller. For controlling any process, initially a mathematical model is identified, controller is designed and simulated to get the expected process behavior. For the purposes of this study and simulation, a lab-scale non-interacting liquid tank system is being considered. The system's mathematical model is identified, and various conventional methods for designing a PI controller is implemented. The efficiency of various computing methods is demonstrated both in simulation and in real time using Simulink software, and the simulation results of conventional algorithms are contrasted. Also, the closed loop performance indices are tabulated and compared. The simulation results that the computational PI controller shows good setpoint tracking and performance.